Faktor-faktor sosial ekonomi yang mempengaruhi keterlibatan penduduk lanjut usia dalam pasar kerja di Provinsi Jambi - Junaidi Junaidi; Erfit Erfit; Purwaka Hari Prihanto (Faculty of Social and Political Science, Universitas Airlangga, 2017)
The study aims to analyze: 1) individual characteristics and profession of elderly in Jambi province; 2) socioeconomic factors affecting involvement of elderly in labor market. Data used in this study is from “raw data” National Socio-Economic Survey or Survei Sosial Ekonomi Nasionnal (SUSENAS) of Jambi Province in 2015. The results of the study reveals: 1) the number of elderly working is relatively large. Nearly half (48,99 percent) of elderly have working as their main activity; 2) the characteristics of elderly who work are: a) predominant in rural areas; b) predominant by men; c) generally has status as the head of the family; d) generally less educated (only graduate from primary school or below); e) mostly working in agricultural with a relatively long working hours; 3) The results of binary logistic regression show that age, sex, education, marital status, status in family, health conditions, and location of rural-urban affect significantly involvement of elderly in labor market.